Osgood Schlatter disease with epiphyseal osteomyelitis, similar and simultaneous: a case report - Simatupang, Mario Daniel; Pramana, I. Gusti Ngurah Alit Oka; Kawiyana, I. Ketut Siki (International Journal of Research in Medical Sciences, 2020)
Osgood-Schlatter disease (OSD) is a condition in which inflammatory reaction happened the patellar tendon insertion on the tibial tuberosity, whereas osteomyelitis is a bone infection which can occur in any bone exposed to bacteria. Both Osgood-Schlatter and osteomyelitis share the same clinical manifestation such as pain and swelling. We present a case of OSD accompanied with epiphyseal osteomyelitis on the left knee. A 12 years old male coming with gradually increasing pain and swelling on the anterior aspect of the left knee. There was swelling and quadricep femoris muscle atrophy, tenderness and bony prominence on the left tibial tuberosity. Knee X-rays confirmed OSD on the left knee, while knee Magnetic resonance imaging (MRI) showed marrow changes on the left tibia epiphysis and patella, as well as increased intensity of patellar ligament, patellar fat pad, with surrounding edema. He was given broad spectrum antibiotic, non-steroid anti-inflammatory drugs (NSAIDs), and physiotherapy to improve the quadriceps, hamstring, and gastrocnemius muscle. Patient’s Visual analogue scale (VAS) score and knee range of motion improved after several weeks. It was believed that repetitive trauma and inflammation which cause OSD, could also cause epiphyseal osteomyelitis due to its nidus site of infection. The colonization can be promoted by prior inconsequential trauma that causes metaphyseal hematoma, which could explain the appearance of both Osgood-Schlatter and epiphyseal osteomyelitis in this presented case. Thorough examination is needed in diagnosing patient with OSD accompanied with osteomyelitis.